Antigen stimulated IgM secretion by circulating B lymphocytes in patients with benign and malignant IgG gammopathy. Relationship to stage of disease. - Pollack, S (1989)
In the present investigation antigen-driven (sheep red blood cells, SRBC) IgM antibody secretion by B lymphocytes of 22 MM (IgG kappa) patients and 15 patients with IgG kappa monoclonal gammopathy of undetermined significance (MGUS) was studied and compared to that of 20 age-matched healthy controls and five patients with Waldenstrum (IgM) macroglobulinemia (WM). Antibody production by cultured lymphocytes of MM and WM patients was significantly decreased, whereas in MGUS patients it fell within normal limits. We could divide MM patients into three subsets: those who secrete normal amounts of IgM in vitro (patients with the stable type); a second subset of patients whose B lymphocytes secreted low amounts of IgM (MM patients in remission); and a third subset of patients who manifested an intrinsic block of B cell differentiation into IgM-secreting cells (patients with the progressive stage). Sephadex G-10 adherent suppressor cells had no effect on antibody production in the stable and progressive types of disease, whereas in the remission stage they markedly inhibited IgM secretion. Measurement of antigen-driven IgM antibody secretion might help in the differentiation of MGUS and stable (smouldering) MM from frank (progressive) MM at diagnosis. It may also provide a tool for monitoring progression of disease and response to therapy.